2022
DOI: 10.1038/s41564-021-01030-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-kingdom microbiota analyses identify bacterial–fungal interactions and biomarkers of colorectal cancer across cohorts

Abstract: Despite recent progress in our understanding of the association between the gut microbiome and colorectal cancer (CRC), multi-kingdom gut microbiome dysbiosis in CRC across cohorts is unexplored. We investigated four-kingdom microbiota alterations using CRC metagenomic datasets of 1,368 samples from 8 distinct geographical cohorts. Integrated analysis identified 20 archaeal, 27 bacterial, 20 fungal and 21 viral species for each single-kingdom diagnostic model. However, our data revealed superior diagnostic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 53 publications
7
124
2
Order By: Relevance
“…ARF18, Phanerochaete chrysosporium, Aspergillus flavus, Fusarium pininemorale, Raffaelea quercus mongolicae, Tilletia controversa, Candida versatilis, Exophiala mesophila, Pseudocercospora pini densiflorae , and Brettanomyces anomalus ) also displayed strong diagnostic performance. Notably, a recent study using a CRC metagenomic dataset, analyzing 1,368 samples from 8 distinct geographical cohorts, also showed an excellent diagnostic value of gut fungi for CRC ( Liu N. N. et al, 2022 ). Therefore, the study of gut mycobiome offers new ideas for diagnosing CRC.…”
Section: Gut Mycobiota and Gastrointestinal Neoplasmsmentioning
confidence: 99%
“…ARF18, Phanerochaete chrysosporium, Aspergillus flavus, Fusarium pininemorale, Raffaelea quercus mongolicae, Tilletia controversa, Candida versatilis, Exophiala mesophila, Pseudocercospora pini densiflorae , and Brettanomyces anomalus ) also displayed strong diagnostic performance. Notably, a recent study using a CRC metagenomic dataset, analyzing 1,368 samples from 8 distinct geographical cohorts, also showed an excellent diagnostic value of gut fungi for CRC ( Liu N. N. et al, 2022 ). Therefore, the study of gut mycobiome offers new ideas for diagnosing CRC.…”
Section: Gut Mycobiota and Gastrointestinal Neoplasmsmentioning
confidence: 99%
“…Two studies on colorectal cancer have demonstrated modifications in the fungal microbiota community and in the networks of inter-kingdom interactions suggesting a possible link between disease and the equilibrium of these two microbial communities. 133 , 134 However, the mechanisms behind these interactions are not yet fully understood, but can be the results of a complex exchange of metabolites. Although, specific bacterial-fungal metabolic interactions have been related to the occurrence of pathologies in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bacteria, non-bacterial microorganisms, including viruses, fungi, archaea and parasites, likely play pathogenic roles in various cancer types, including CRC 33 34. Viruses represent an essential component of the intestinal microbial community and have been implicated in inflammatory bowel diseases35 36 and CRC 34 37 38.…”
Section: Tumour Microenvironmentmentioning
confidence: 99%